2006
DOI: 10.1007/s10072-006-0561-7
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal photochemotherapy: a safety and tolerability pilot study with preliminary efficacy results in refractory relapsing-remitting multiple sclerosis

Abstract: Extracorporeal photochemotherapy (ECP) is an immunomodulating procedure consisting of autologous reinfusion of peripheral blood mononuclear cells (PBMC) after direct exposure to 8-methoxy-psoralen and UV-A. It has been described as a successful treatment for different T-cell-mediated diseases and preliminary results suggest that ECP might be effective in the treatment of relapsing-remitting multiple sclerosis, but does not significantly alter the course of the progressive form of MS. In this study, we report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 19 publications
0
20
0
3
Order By: Relevance
“…Extracorporeal PBMC exposure (ECP) to 8-MOP and UVA Weak response in children with diabetes [172,200] Multiple sclerosis Extracorporeal PBMC exposure (ECP) to 8-MOP and UVA Well tolerated, reduced relapse rate in 5 patients with relapsing-remitting MS [201] Moderate efficacy in chronic progressive MS patients with rebound after treatment discontinuation [202] 8-MOP 8-methoxypsoralen, AA alopecia areata, ALA 5-aminolaevulinic acid, BPD-MA benzoporphyrin derivative monoacid, ECP extracorporeal photochemotherapy, GVHD graft versus host disease, GVL graft versus leukemia, MS multiple sclerosis, m-THPC meta-tetrahydroxyphenylchlorin, PBMC peripheral blood mononuclear cells, PDP photodynamic purging, PDT photodynamic therapy PDT-based cancer vaccines…”
Section: Photoimmunotherapy and Pdt-mediated Immunomodulationmentioning
confidence: 99%
“…Extracorporeal PBMC exposure (ECP) to 8-MOP and UVA Weak response in children with diabetes [172,200] Multiple sclerosis Extracorporeal PBMC exposure (ECP) to 8-MOP and UVA Well tolerated, reduced relapse rate in 5 patients with relapsing-remitting MS [201] Moderate efficacy in chronic progressive MS patients with rebound after treatment discontinuation [202] 8-MOP 8-methoxypsoralen, AA alopecia areata, ALA 5-aminolaevulinic acid, BPD-MA benzoporphyrin derivative monoacid, ECP extracorporeal photochemotherapy, GVHD graft versus host disease, GVL graft versus leukemia, MS multiple sclerosis, m-THPC meta-tetrahydroxyphenylchlorin, PBMC peripheral blood mononuclear cells, PDP photodynamic purging, PDT photodynamic therapy PDT-based cancer vaccines…”
Section: Photoimmunotherapy and Pdt-mediated Immunomodulationmentioning
confidence: 99%
“…These results suggest that prophylactic administration of treated donor lymphocytes may be an ideal method of enhancing posttransplant immunity in recipients of allogeneic BMT: a method of adoptive cellular immunotherapy that avoids the thymic damage associated with GVHD while producing a protective antiviral effect. Photo-activated amotosalen-DNA crosslinked treatment of T cells is an established treatment process that has already been used in human to treat cutaneous T cell lymphoma, GvHD, and autoimmune disease (53)(54)(55). The present data demonstrating the antiviral activity and lack of toxicity following prophylactic adoptive cellular immunotherapy using amotosalen-treated donor lymphocytes suggests that clinical trials of this approach in patients undergoing allogeneic BMT may be warranted.…”
Section: Discussionmentioning
confidence: 77%
“…A preliminary double-blind, placebo-controlled trial of ECP using 8-MOP found this therapy to be a safe and tolerable method, but it did not affect significantly the course of chronic progressive multiple sclerosis and in secondary forms could only transiently improve the clinical picture [162]. However, in a more recent pilot study with patients with relapsing-remitting multiple sclerosis, ECP was also a safe and tolerable technique suggesting that this treatment might be useful as a therapeutic alternative in patients not responsive to or not eligible for traditional immunomodulating or immunosuppressive treatments [163].…”
Section: Noncutaneous Autoimmune Diseasesmentioning
confidence: 93%